Penerapan Penghimpunan Dana Nasabah Pada Akad Wadi’ah Di BMT NU Cabang Blutoh Sumenep - Abdussakur Abdussakur; Kristiani Utami (Journal of Islamic Banking, 2022)
Wadi'ah in principle is to help the custodian, and the party entrusted with his position as a helping party. Therefore, the nature of wadi'ah is trust. In the book I'anatut Thalibin by Ad Dimyathy it is explained that wadi'ah is: "A contract that aims to protect a property." In carrying out wadi'ah practices, customer funds deposited in Islamic financial institutions are guaranteed safe, and Islamic financial institutions are required to bear all risks that occur in customer funds. Wadi'ah in Islamic financial institutions is not the wadiah described in fiqh books. Wadi'ah that is currently practiced is more relevant to the law of receivables, because the Financial Institutions use customer money in various projects. The existence of the authority to use the goods, own the results and bear the damage or loss is the main difference between wadi'ah and dain (debts). Thus, if these three characters have been embedded in the wadi'ah contract, then in fact and legally this contract turns into a debt and credit contract and not a wadi'ah contract.